The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/nhs.12852
|View full text |Cite
|
Sign up to set email alerts
|

Nurse‐led counseling for coronary artery disease patients: A 1‐year follow‐up study

Abstract: Nurse‐led counseling and systematic follow‐up have been shown to reduce cardiovascular risk factor levels. The study aims were to investigate if cardiovascular risk factor levels could be reduced in patients with coronary artery disease with a nurse‐led intervention and to report patients' evaluations of nurse‐led counseling. The study design was a real‐life longitudinal follow‐up counseling intervention. Data were collected from November 2017 to May 2020. The nurse‐led intervention and patients’ follow‐up tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…For this reason, it is important that intensive, comprehensive follow-up is carried out during the first months after the event to improve CVRFs and morbidity and mortality rates. As in previous studies, it has been observed that better results are obtained in this period, enabling patients to improve some of their CVRFs (Huang et al, 2017;Jafari et al, 2020;Nurmeksela et al, 2021;Ruiz-Bustillo et al, 2019), their self-efficacy (Polsook et al, 2016), and their levels of empowerment (Lei et al, 2018). Kim et al confirmed that it is essential to periodically monitor the direct effect of self-care compliance on changes to left ventricular ejection fraction in outpatients after AMI.…”
Section: Discussionmentioning
confidence: 77%
“…For this reason, it is important that intensive, comprehensive follow-up is carried out during the first months after the event to improve CVRFs and morbidity and mortality rates. As in previous studies, it has been observed that better results are obtained in this period, enabling patients to improve some of their CVRFs (Huang et al, 2017;Jafari et al, 2020;Nurmeksela et al, 2021;Ruiz-Bustillo et al, 2019), their self-efficacy (Polsook et al, 2016), and their levels of empowerment (Lei et al, 2018). Kim et al confirmed that it is essential to periodically monitor the direct effect of self-care compliance on changes to left ventricular ejection fraction in outpatients after AMI.…”
Section: Discussionmentioning
confidence: 77%
“…El modelo causal reportado evidencia que las variables: control personal, severidad de los síntomas y evaluación cognitiva inuyen en la evaluación de los síntomas, lo que determina la respuesta reejada en la toma de decisiones. Con ello se conrma su correlación bidireccional, tal como lo plantea el MCMS (21)(22)(23)(24). Como respaldo a esto, otros estudios similares (25)(26) documentan que cuando la persona entiende su enfermedad como una condición crónica que se puede agudizar, esto le permite evaluar mejor los síntomas, otorgándole mayor control en la toma de decisiones frente a nuevos eventos coronarios.…”
Section: Discussionunclassified